Analisis UMKM Kuliner dalam Mendukung Pembangunan Berkelanjutan (Studi Kasus UMKM Kecamatan Medan Tembung) - Andani, Nadzira Putri; Amelia, Cahya; Lubis, Rizky Aulia; Irwansyah, Irwansyah; Suharno, Muhammad Iqbal (Innovative: Journal Of Social Science Research, 2024)
Culinary MSMEs in Medan Tembung District have significant potential to support regional economic growth. This research uses SWOT analysis to determine the external and internal elements influencing industrial innovation. The findings indicate that MSMEs in Medan Tembung excel in creativity, local wisdom, and flexibility, but are hampered by limited capital, lack of modern management knowledge, and inconsistent product quality. Key opportunities include increasing public interest in local products, developments in information technology, and government support, while threats include intense competition, changes in consumer preferences, and economic uncertainty. Strategic recommendations include product innovation, enhancing human resource quality and making use of digital technology for marketing.